Ibn Khaldun and Confucius: A Preliminary Comparative Analysis between 'Asabiyyah and Wu Lun - Abdul Karim, Abdul Halim (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Ibn Khaldun and Confucius: A Preliminary Comparative Analysis between 'Asabiyyah and Wu Lun